Gastric Cancer Genetics and Its Implications for Diagnosis, Prognosis, and Treatment of the Disease - José Pedro Santos; Joana Figueiredo; José Carlos Machado (Yong Chan Lee, 2024)
Gastric cancer (GC) is an aggressive disease and the fifth most common cancer worldwide with a variable geographical distribution. GC has a very low survival rate, mainly because of its heterogeneous presentation, multifactorial etiology, and late diagnosis. It is well established that various risk factors contribute to the development of the disease, including salty diet, smoking, and excessive alcohol consumption. Importantly, interactions between genetic and environmental traits trigger the activation of key signaling pathways, influencing gastric cell behavior towards neoplastic transformation and progression. Despite important advances in our understanding of GC, it remains a major health burden owing to epidemiological and therapeutic limitations. This study aimed to provide a comprehensive overview of the genetic landscape of GC phenotypes and molecular biomarkers for diagnosis and prognosis. In particular, we discuss the advances in genomic knowledge and technology that have yielded comprehensive information on the genetics of GC and classified it from a histological to a molecular perspective. Therefore, targeted and immune-based therapies have been developed, highlighting the challenges associated with intratumoral and interpatient heterogeneity. Finally, we explored potential research avenues on the intricacies of GC and identified accurate biomarkers for improved cancer screening and stratification. The development of innovative approaches to tackle relevant molecules is needed for GC management.